Choosing the best teaching modality: medical students’ perspectives - Panchu, Pallavi; Suseel, Appu; George, Tijo (International Journal of Research in Medical Sciences, 2019)
Background: Didactic mode of teaching retains a strong hold in the Indian medical education scenario. Is this because there is no alternative teaching method or is it the preferred choice of the learners? When outcomes of teaching are considered, better teaching tools are available. But when the question of choice of the learners is raised, there are no satisfactory answers. This study aims to expose medical students to different modalities of training and to obtain their verdict on what they consider is the best method of teaching to aid in their learning process. Methods: A cross sectional study was conducted on all I year medical students after obtaining institutional clearance. 33 students consented to participate in the study. They were divided into 3 groups and given instructions in cardiopulmonary resuscitation (CPR)- single rescuer method in the didactic, video format and manikin based. A pre-test was taken and a post-test too. A skills test was taken at the end of teaching. Finally, all the students were asked to give a feedback. The results tabulated and analyzed. Results: Students with simulation (manikin) based teaching had more confidence in performance of CPR, performed better in the skills test and post-test when compared to the other groups. Almost unanimously, the students preferred simulation based teaching over the other two tools that they were exposed to. Conclusion: A revolution in medical teaching in the Indian syllabus is the need of the hour. While newer tools are being implemented, the requirements and choices of the recipients of teaching should also be considered.